HUBUNGAN PENGETAHUAN, SIKAP IBU HAMIL, DAN DUKUNGAN SUAMI TERHADAP KEJADIAN HIPEREMISIS GRAVIDARUM DI PUSKESMAS SIMPANG TIGA KECAMATAN BUKIT KABUPATEN BENER MERIAH TAHUN 2024 - Haira, Halma; Hudnah, Hudnah; Yusran, Mawadhah; HS, Nurlaely (Jurnal Ilmiah Cerebral Medika, 2024)
ABSTRACT Hyperemisis Gravidarum is excessive nausea and vomiting in pregnant women. Hyperemisis Gravidarum is nausea and vomiting that occurs in early pregnancy until 20 weeks of gestation, where everything that is eaten and drunk is vomited up so that it can affect the general condition, weight loss and severe dehydration. This research used the Descriptive Analytical method with a Cross sectional approach, the population in this study was all 403 pregnant women at the Simpang Tiga Community Health Center. The sample in this study is part of or represents the entire population to be studied, totaling 80 pregnant women. By using the Slovin Formula, analyze the sampling technique using Accidental Sampling. The Analysis in this study used chi-square analysis. The research result showed tahat the factors related to Hyperemisis Gravidarum were knowledge (p-value=0,027) and attitude (p-value=0,028). It is hoped that this research can serve as input for pregnant women in preventing the occurrence of Hiperemisis Gravidarum by recommending changing their daily diet in small amounts, but more frequently. Keywords : Knowledge, Attitude, Husband’s Support